Entrepreneurial Modes towards Information Technology Applications in Business during Pandemic Covid-19 Based on Indonesia SMEs’ Stories - Robertus In Nugroho Budisantoso; Antonius Sumarwan (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2022)
This paper aims to identify entrepreneurial modes towards information technology applications in business during pandemic Covid-19 based on Indonesia SMEs’ stories. This study uses phenomenological approach in discerning 33 Economics students’ reports on SMEs’ ways in relating to social media platforms in the midst of the pandemic as relatively different business instruments driven by information technology along with their encounters to new opportunities within novel landscape of business. The reports indicate a general pattern of three critical stages linked to entrepreneurial challenges namely in the first stage business distortion, in the middle efficiency calculation, and finally available resources allocation. Using two factors i.e. learning capability of the business actors and the sophistication degree of information technology applications, the ways through which entrepreneurs relate to information technology within pandemic context can be identified into four types of mode namely adoption, adaptation, aversion, and abandon. Most of them are in adoption mode, few are in adaptation and abandon modes, and none in aversion mode.